Types of decorations, their social meaning and influence on moral injury: A mixed methods approach - Ruud Lathouwers; Tine Molendijk (PLoS ONE, 2025)
Research on moral injury has thus far paid little attention to social factors and cultural elements. This study addresses this gap by examining the effects of one particular cultural artefact on moral injury that is typical of armed forces, (military) decorations, including awards and medals. Through a preregistered experiment involving two scenarios—omission of helping behavior and commission of mortar fire—resulting in civilian deaths, we manipulated the factors self-attribution versus attribution of blame to others/the system and the presence or absence of a decoration. Moreover, we conducted seven qualitative interviews. Contrary to our expectations, none of the experimental conditions within the scenarios yielded significant differences. However, the scenarios themselves differed significantly from each other, indicating that wrongful inaction may have a stronger effect on moral injury than wrongful action. The subsequent qualitative interviews ( N = 7) revealed nuanced insights, suggesting that the effects of decorations on moral injury may vary. Cases were discerned in which military decorations demonstrated the potential to either alleviate or exacerbate moral injury. This dynamic depended on factors such as an individual’s assessment of the justifiability of the act for which they received the decoration, and the perceived authenticity of the decoration’s bestowal – whether it was experienced as a genuine acknowledgment or merely a superficial gesture. These findings indicate a possibly complex interplay of cultural artifacts and moral injury within military contexts.